Modification of Gelatin by Ciprofloxacin for Industrial Applications - Dina S. Ahmed; Mustafa Abdalla; Ahmed Al-Ani; Yousif, Emad (Journal of Sustainable Materials Processing and Management, 2024)
Non-degradation of plastic materials have great impact on the environment and become a universal issue. So that, there is a necessity for environmentally friendly biomaterials as alternative materials of those have a non-degradable properties. Non-synthetic materials such as proteins and polysaccharides considered as a replacement materials of a non-degradable materials due to their ability to bio degradation properties. Gelatin considered one of the most candidate polymer for this purposes and can be synthesized by collagen hydrolysis. Gelatin can be used in different industries specifically in food packaging because of its ability to form film and gelling properties, low cost and biocompatible material. In this research, gelatin was modified with ciprofloxacin and the synthesized materials characterized by Fourier transform infrared (FTIR) and the surface was imaged by scanning electron microscopy (SEM).